Risk factors associated with drug-resistant tuberculosis in prisons in Sāo Paulo State, Brazil (2006-2016) - Juliane de Almeida Crispim; Luiz Henrique Arroyo; Thaís Zamboni Berra; Felipe Lima dos Santos; Ludmilla Leidianne Limirio Souza; Yan Mathias Alves; Antônio Carlos Vieira Ramos; Alexandre Tadashi Inomata Bruce; Mellina Yamamura; Alessandro Rolim Scholze; Hamilton Leandro Pinto de Andrade; Flávia Meneguetti Pieri; et al. (Journal of Infection in Developing Countries)
Introduction: Prisons are high-risk settings for drug-resistant tuberculosis because the prevalence of the tuberculosis (TB) is much higher than in the general population. This study to investigated the factors associated with drug-resistant tuberculosis in prisons in the state of São Paulo, Brazil.